Strategi Service Quality Sebagai Media Dalam Menciptakan Kepuasan Dan Loyalitas Pelanggan - Nik Haryanti; Diyanus Abdul Baqi (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2019)
Quality of service is one of the factors that determine customer satisfaction. The good quality of service and its effectiveness in carrying out the promotion mix will provide positive responses to customer satisfaction to remain loyal using its services. The creation of customer satisfaction can provide several benefits, including the relationship between the company and the customer to be harmonious, provide a good basis for repurchase and create customer loyalty and form word-of-mouth recommendations that benefit the company. This means that the existence of a good quality of service will be a driving factor for increasing consumer satisfaction so that there will be repeated consumption of products sold until consumer loyalty is created. This type of research uses library research or library research. Literature research is a study conducted in a library room to collect and analyze data sourced from libraries in the form of periodical books such as periodicals, periodicals, historical stories, documents and other library materials that are can be used as a reference source for compiling a scientific report. Data analysis techniques used content analysis. The results of this study prove that loyalty will be created by maintaining an image through creating a good perception of product attributes and implementing a service recovery program by apologizing for making mistakes, taking immediate action, showing remorse, providing guarantees and following up. Besides creating customer satisfaction is a variable that cannot be left behind in order to create a reason for customers to remain willing to establish long-term relationships with the company. Keywords: service quality, satisfaction, loyalty